2020
DOI: 10.1097/dcr.0000000000001611
|View full text |Cite
|
Sign up to set email alerts
|

Peer Support as an Ideal Solution for Racial/Ethnic Disparities in Colorectal Cancer Screening: Evidence from a Systematic Review and Meta-analysis

Abstract: BACKGROUND: Low implementation of colorectal cancer screening in ethnic minorities is the main reason for racial and ethnic disparities in colorectal cancer morbidity and mortality. Peer support is widely used for promoting health care in ethnic minorities. However, whether it improves their acceptance to undergo the screening remains controversial. OBJECTIVE: We performed a meta-analysis of the currently available studies to further explore its effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 45 publications
0
27
1
Order By: Relevance
“…Through the mediation analyses, we found that social networking participation fully mediates the negative impact of online health information seeking on effective screening. However, this result is inconsistent with some previous studies which showed that social media engagement could promote positive healthy behavior [38][39][40].…”
Section: Determinants and Mechanisms Of Ccscontrasting
confidence: 99%
“…Through the mediation analyses, we found that social networking participation fully mediates the negative impact of online health information seeking on effective screening. However, this result is inconsistent with some previous studies which showed that social media engagement could promote positive healthy behavior [38][39][40].…”
Section: Determinants and Mechanisms Of Ccscontrasting
confidence: 99%
“…Nonetheless, there were promising positive effects on stress management, quality of life and healthy behaviors. This study was followed [73] by a systematic review and meta-analysis of peer counselling to compensate for racial/ethnic disparities in colorectal cancer screening. Low implementation of such screening in ethnic minorities was the main reason for disparities in morbidity and mortality.…”
Section: Medical Conditionsmentioning
confidence: 99%
“…Previous systematic reviews on effectiveness of peer support provide limited evidence or do not focus exclusively on empowerment dimensions, cancer and peer support. 10,[32][33][34][35][36][37][38][39][40] Therefore, the aim of the present systematic review is to provide an overview of findings from observational and interventional studies regarding the association of participation in cancer PSGs and/or dyadic peer support with the empowerment dimensions as defined by Zimmerman. This review has conceptually been guided by three preliminary considerations. Firstly, untrained peer leaders often feel overstrained in meeting the complex needs of leadership.…”
mentioning
confidence: 99%